Pendidikan Kesehatan tentang Meningkatkan Pengetahuan Status Gizi pada Remaja di Madrasah Aliyah Negeri Sampang - Ida Wahyuni; Tri Nili Sulayfiyah; Mery Eka Yaya Fujianti (PPNI UNIMMAN, 2024)
Balanced nutrition is a daily food composition that contains nutrients in types and quantities that suit the body's needs, taking into account the principles of food diversity, physical activity, clean living behavior and monitoring body weight regularly in order to maintain a normal body weight to prevent nutritional problems. and maintain the immune system in the body. Adolescence is a transition period from childhood to adulthood, where physical, emotional and psychological changes occur. To achieve optimal growth, adequate nutritional intake is needed. A diet with balanced nutrition is one of the main factors in the complex nutritional problems in Indonesia. People need to get clear and adequate information about a diet with balanced nutrition, including eating a variety of foods (eating vegetables and fruit), clean living behavior, physical activity, and regularly weighing yourself as a component of a balanced lifestyle. Basically, nutritional problems in adolescents arise due to incorrect nutritional behavior, namely an imbalance between nutritional consumption and recommended nutritional adequacy. Nutritional condition or nutritional status is a description of what is consumed over a long period of time. The nutritional condition can be in the form of undernutrition, good or normal or overnutrition. Deficiency of one nutrient can cause disease in the form of deficiency disease. If deficiencies within marginal limits cause milder disorders or decreased functional ability.